Linguistic heterogeneity as a means to communicate war experience in Philip Caputo’s A Rumor of War - Kujawska-Lis, Ewa (Studia Anglica Posnaniensia, 2025)
Philip Caputo’s A Rumor of War is a fictionalised autobiographical story that presents war from the perspective of one of its participants. In order to suffuse his text with verisimilitude, Caputo introduces various languages and their varieties, ranging from dialectal variations of American English and the professional jargon of the US marines to inclusion of other languages, such as French and Vietnamese, as well as Japanese and American pidgin English. This linguistic heterogeneity, quite different from Bakhtin’s polyphony, as the different languages do not have the same status in the memoir, serves to authenticate the story, to reflect the realities of this particular war, and to personalise characters, indicating their social and ethnic backgrounds. It also affects the reception of the text depending on the experience of the readers (the knowing and unknowing audience). Language in this case creates a bond of war experience with some readers (those who are/were familiar with the realities of Vietnam) while, paradoxically, generating some emotional distance for others. Additionally, the author provides each chapter with an epigraph, mostly quotes from English-language literature, and in particular the Great War poets Wilfred Owen and Siegfried Sassoon, thus further diversifying the linguistic landscape of the text and universalising war. The purpose of this analysis is to explore linguistic heterogeneity (understood as the employment of different languages and their varieties) in Caputo’s memoir to pinpoint the aforementioned functions. Methodologically, the analysis is primarily based on the close reading of selected passages that include linguistic varieties to indicate their effects. It looks at how Caputo operationalises language varieties to achieve specific outcomes in his work treated as a linguistically heterogenous text, whereby the employment of particular varieties does not equal the empowerment of characters or minority groups they represent and does not necessarily provide their perspectives on that war.